Poems and World War II narrative of Robert Thomson - Thomson, Robert
Volume of handwritten copies of poems written during Thomson's travels in the United States during the 1930s; and notebook containing a narrative entitled "When We Landed the Yanks at Oran" describing his experiences on a troop ship during the British invasion of North Africa, December 8, 1942.
British poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: English poetry; World War, 1939-1945 -- Algeria; World War, 1939-1945 -- Campaigns -- Africa, North; Oran (Algeria) -- History; United States -- Description and travel; Poets